6x-3=5+4x

Simple and best practice solution for 6x-3=5+4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x-3=5+4x equation:


Simplifying
6x + -3 = 5 + 4x

Reorder the terms:
-3 + 6x = 5 + 4x

Solving
-3 + 6x = 5 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + 6x + -4x = 5 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-3 + 2x = 5 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + 2x = 5 + 0
-3 + 2x = 5

Add '3' to each side of the equation.
-3 + 3 + 2x = 5 + 3

Combine like terms: -3 + 3 = 0
0 + 2x = 5 + 3
2x = 5 + 3

Combine like terms: 5 + 3 = 8
2x = 8

Divide each side by '2'.
x = 4

Simplifying
x = 4

See similar equations:

| 3x-7=x+21 | | 2(x-3)=1.5(x-4)+x | | 5(z-4)=4z-20 | | 8p=7p | | 0=120-4.9t^2 | | 4n+17+n-2=180 | | 5(9+6)=8p | | (x-16)/3=3x | | Y=6x-17 | | x^2+3x-2.5=0 | | -4x-5y=17 | | 180n-360=s | | x^3-x^2+8x+6=0 | | 3z^3-24z^2+36z=0 | | 6x+17-x=135 | | 12k+6.5=k+15 | | 2*t^2-12t+97=0 | | 12(2-4x)=20(1-2x)-15x+3 | | 12(2-4x)=20(1-2x)-15x+13 | | 9-8k=0 | | 6x-5+7x+3=180 | | (b-g)(b-g)=0 | | 6x+13=2x+11 | | 9a^2+30at+25t^2= | | 3(5-r)-(15-r)=17 | | 6t-12=2t+2 | | (8+x)(8+x)=0 | | 5(4x+7)=120 | | 2(x+2)+6x=2-5x | | 5y-2(y+12)=27 | | 5x-3+6x-1=5-2(x+1) | | -(-2x+2)=14 |

Equations solver categories